A Comprehensive Review of Keratinous Cysts: Etiology, Diagnosis, and Management - Qabas M Hameed Al Anni; Hassan, Ramzy Kaddim; Qasim Abdulrasol Mohammed; Diyar Iqbal Kadhim (Indonesian Journal on Health Science and Medicine, 2025)
Keratinous cysts, predominantly referred to as epidermoid cysts (ECs) or epidermal inclusion cysts (EICs), represent the most prevalent subtype of cutaneous cysts. These benign, slow-growing lesions are defined by a pathological cavity situated within the dermis or subcutis, lined by stratified squamous epithelium and filled with macerated keratin and lipid-rich debris. While often asymptomatic, their clinical significance arises from a high frequency of complications, including inflammation, infection, and rupture, which prompt medical consultation. Furthermore, their presentation can mimic a wide range of other soft tissue tumors, necessitating accurate diagnosis. This paper provides a exhaustive, systematic review of keratinous cysts, delving into their historical context, precise nomenclature, and epidemiological patterns. It elaborates on the multifactorial etiologies and molecular pathways underpinning their pathogenesis. The clinical and histopathological features are described in detail, alongside advanced diagnostic imaging characteristics. A critical analysis of the differential diagnosis is presented, followed by a comprehensive discussion on management strategies, from conservative approaches to sophisticated surgical techniques aimed at minimizing recurrence and optimizing cosmetic outcomes. The paper also explores rare associations and future research directions, consolidating current evidence to serve as a definitive reference for dermatologists, surgeons, and primary care physicians. condition. Highlights: 1. Keratinous cysts, including epidermoid and epidermal inclusion cysts, are the most common cutaneous cysts with significant clinical impact when complicated. 2. Accurate diagnosis requires distinguishing them from other cystic and tumor-like lesions using clinical, histological, and imaging features. 3. Management ranges from observation and intralesional corticosteroids to complete surgical excision, with prognosis generally excellent after definitive treatment.